2016
DOI: 10.1245/s10434-016-5437-3
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Locoregional Recurrence in Women with Early-Stage Breast Cancer

Abstract: For premenopausal women with invasive breast cancer who undergo BCT, BMI is an independent prognostic factor for LRR. If confirmed, these findings suggest that more aggressive treatment strategies may be warranted for these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
0
31
1
Order By: Relevance
“…This would allow us to carry out multidisciplinary interventions to prevent excess weight and a prevalence of obesity. Obesity is associated with lower survival rates in breast cancer (Druesne‐Pecollo et al., ), in postmenopausal cancer and in premenopausal cancer, as suggested by recent studies (Chan et al., ; Warren et al., ). It would seem that more studies are necessary with regard to the QoL of women with cancer with immediate breast reconstruction, taking other variables into account apart from the surgical variables.…”
Section: Discussionmentioning
confidence: 84%
“…This would allow us to carry out multidisciplinary interventions to prevent excess weight and a prevalence of obesity. Obesity is associated with lower survival rates in breast cancer (Druesne‐Pecollo et al., ), in postmenopausal cancer and in premenopausal cancer, as suggested by recent studies (Chan et al., ; Warren et al., ). It would seem that more studies are necessary with regard to the QoL of women with cancer with immediate breast reconstruction, taking other variables into account apart from the surgical variables.…”
Section: Discussionmentioning
confidence: 84%
“…Although the association between obesity/overweight and the prognosis of breast cancer patients remains controversial, it has been reported that impact of BMI on prognosis of breast cancer may relate to menopausal status. [ 15 ] To identify this issue, we conducted a stratified analysis according to the menopausal status.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous study, the effects of higher BMI on prognosis of breast cancer may be associated with menopausal status. [ 15 ] Berclaz et al [ 9 ] demonstrated that elevated BMI is significantly associated with a worse prognosis of breast cancer, especially for premenopausal and perimenopausal patients, and Kawai et al [ 16 ] found that higher BMI (BMI ≥25.8 kg/m 2 ) was associated with an increase in mortality for premenopausal patients. In a cohort study, obese postmenopausal women at diagnosis were at increased risk of breast cancer mortality compared to normal weight women after 6-year follow-up, while being overweight did not affect survival.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between BMI and prognosis have already been demonstrated in some malignant tumors, primarily breast and prostate cancers. Patients with high BMIs at the time of breast cancer discovery have significantly increased risk of distant recurrence (21,22) and overall mortality (23). In one particular meta-analysis, higher BMI values were implicated in breast cancer incidence (24).…”
Section: Discussionmentioning
confidence: 99%